Landasan Teori Pendidikan Karakter Berbasis Pendidikan Agama Islam - Daryaman, Daryaman; Hasanah, Aan; Arifin, Bambang Samsul; Firdaus, Janatun; Kameswara, Dhika (Bestari, 2021)
Character education is not only a focus in the world of education in general, but in the view of Islam Character education is one of the important teachings that must be carried out by every individual Muslim. Character education is an important thing to be known, owned and practiced by humans. Character education in Indonesia has long been rooted in educational traditions. The ideal human being is one who has the power of reason and noble character. That is the man who will save himself, his family, nation, and country. The research method used is a qualitative method where the researcher's activities include understanding, analyzing and conducting a more accurate study with conceptualization and implementation of character education foundations. Education must understand efforts to cultivate intelligence in the form of thoughts both in the minds of students, appreciation and understanding in reason and practice in the form of behavior. The axiological foundation of character education will equip educators to think clearly about the relationship between life goals and character education so that they will be able to provide guidance in developing an educational program related to the realities of the global world.